Death becomes her : original Broadway cast recording [compact disc] - Mattison, Julia; Carey, Noel; Pennette, Marco (Concord Theatricals Recordings, 2025)
Madeline Ashton and Helen Sharp have always been the best of frenemies, until Madeline steals Helen's fiancé. After sipping a magical potion, Madeline and Helen begin a new era with their youth and beauty restored...and a grudge to last eternity. Starring Tony nominees Megan Hilty, Jennifer Simard and Christopher Sieber, and Grammy-winner Michelle Williams, Death Becomes Her, based on the 1992 film, is a drop-dead hilarious new musical about burying the hatchet...again, and again, and again.